2008
DOI: 10.1186/1471-2288-8-36
|View full text |Cite
|
Sign up to set email alerts
|

The changing causal foundations of cancer-related symptom clustering during the final month of palliative care: A longitudinal study

Abstract: Background: Symptoms tend to occur in what have been called symptom clusters. Early symptom cluster research was imprecise regarding the causal foundations of the coordinations between specific symptoms, and was silent on whether the relationships between symptoms remained stable over time. This study develops a causal model of the relationships between symptoms in cancer palliative care patients as they approach death, and investigates the changing associations among the symptoms and between those symptoms an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
31
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(33 citation statements)
references
References 29 publications
1
31
0
1
Order By: Relevance
“…Não foram encontrados estudos relatando associações entre os DSSs na população de idosos obesos, sendo que os resultados deste trabalho, que envolvem as relações hipotéticas, foram construídos com base em dados de pesquisas com a população idosa, não necessariamente com excesso de peso. No entanto, a metodologia de construção de relações hipotéticas vem sendo adotada em estudos de diferentes áreas 10,61,62 para ser testada em um grupo específico por meio de MEE.…”
Section: Discussionunclassified
“…Não foram encontrados estudos relatando associações entre os DSSs na população de idosos obesos, sendo que os resultados deste trabalho, que envolvem as relações hipotéticas, foram construídos com base em dados de pesquisas com a população idosa, não necessariamente com excesso de peso. No entanto, a metodologia de construção de relações hipotéticas vem sendo adotada em estudos de diferentes áreas 10,61,62 para ser testada em um grupo específico por meio de MEE.…”
Section: Discussionunclassified
“…1 is similar to the model initially proposed by Olson et al [6] but contains their diagnostically prompted emendations (an effect of appetite on well-being at both 1 month and 1 week, and an effect of anxiety on well-being at 1 month before death). Olson et al [6] observed that over 70% of the initially postulated effects were significant at either 1 month or 1 week prior to death, though the operative causal effects differed substantially between 1 month and 1 week prior to death.…”
Section: Introductionmentioning
confidence: 85%
“…Olson et al [6] obtained data for 82 palliative cancer patients from a control database of the Capital Health Regional Palliative Care Program (CHRPCP) in Alberta Canada for the symptoms recorded by the Edmonton Symptom Assessment System (ESAS) between 1995 and 2000. None of the patients were receiving anticancer treatment, but all were receiving symptom control interventions and other supportive and palliative care.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations